Nuclear expression of IL-33 in epidermal keratinocytes promotes wound healing in mice. Issue 2 (February 2017) - Oshio, Tomoyuki; Komine, Mayumi; Tsuda, Hidetoshi; Tominaga, Shin-ichi; Saito, Hirohisa; Nakae, Susumu; Ohtsuki, Mamitaro
Highlights: IL-33 is positively involved in wound healing. IL-33 involvement in wound healing is dependent on nuclear factor kappa B. Nuclear IL-33, but not IL-33 as a cytokine, is involved in wound healing. IL-33 involvement in wound healing is also dependent on re-epithelialization process of keratinocytes. Abstract: Background: Skin is the outermost tissue of the human body, and works as a mechanical, chemical, and biological barrier. The epidermis is the uppermost layer of the skin, and keratinocytes constitute the majority of epidermal cells. Wounds are disruptions of skin integrity, and cause tremendous disadvantages to humans; accordingly, rapid wound healing is very important. Interleukin (IL)-33 is expressed in barrier tissue cells, such as epithelial and endothelial cells. Upon injury, IL-33 is released to stimulate immune cells, functioning as an "alarmin." ST2 is a receptor for IL-33; its soluble form (s)ST2 acts as a decoy receptor and competes for IL-33 binding. Objectives: We aimed to clarify the role of IL-33 in wound healing. Materials and methods: Wild-type (WT), IL-33 knockout (IL33 KO) mice, and sST2 transgenic (Tg) mice were wounded with a 4-mm punch, and the wound healing process was compared. Immunohistochemical analyses were performed to detect macrophages, neutrophils, and mast cells. Total RNA was extracted from the skin samples and real-time PCR was performed. An in vitro scratch wound assay was performed. Results: Wound healing was delayed in IL33 KO mice compared to WT mice, while wound healing in sST2 Tg mice was comparable to that of WT mice. A histological examination showed delayed elongation of the epidermal tongue in IL-33 KO mice. An immunohistochemical study revealed prolonged neutrophilic infiltration at a later stage in IL-33 KO mice. IL-6, IL-1β, and CXCL1 transcripts were more abundant in the wounds of IL-33 KO mice than WT mice. Intraperitoneal administration of an NFκB inhibitor to IL-33 KO mice normalized the delayed wound healing and the enhanced expression of IL-6 in IL-33 KO mice. Epidermal keratinocytes from IL-33 KO mice showed delayed wound closure compared to those from WT mice. Conclusion: Our results indicate that nuclear IL-33, but not IL-33 as a cytokine, has beneficial effects on wound healing in mice, probably by suppressing NFκB to inhibit excessive inflammation and by maintaining keratinocyte proliferation or migration for epithelialization.